A companion to Catalan literature - Terry, Arthur (Colección Támesis. Monografías, 2003)
"This book is the only one of its kind in English. Part literary history, part literary criticism, it is above all a personal assessment of a rich and important body of work which is still not widely known outside Catalonia. Catalan literature, one of the three major Peninsular literatures, reached an impressive level of excellence in the middle ages, beginning with Ramon Llull and the chronicles, and culminating in the two great fifteenth-century writers, the poet Ausias March and Joanot Martorell, the author of Tirant lo Blanc, one of the land-marks in early prose fiction."